2010
DOI: 10.1080/01635581.2010.494335
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Antioxidant Vitamins and Selenium Supplement in Prostate Cancer Prevention: A Meta-Analysis of Randomized Controlled Trials

Abstract: Several studies have evaluated the possible association between antioxidants vitamins or selenium supplement and the risk of prostate cancer, but the evidence is still inconsistent. We systematically searched PubMed, EMBASE, the Cochrane Library, Science Citation Index Expanded, Chinese biomedicine literature database, and bibliographies of retrieved articles up to January 2009. We included 9 randomized controlled trials with 165,056 participants; methodological quality of included trials was generally high. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
50
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(52 citation statements)
references
References 27 publications
1
50
0
1
Order By: Relevance
“…Large amounts of ROS may favor human disease such as cancers, cardiovascular diseases, aging, and neurodegenerative diseases [64]. Therefore, the daily intake of exogenous antioxidants is beneficial for protecting the human body against the destructive effects of free radicals [65,66].…”
Section: Antioxidant Compoundsmentioning
confidence: 99%
“…Large amounts of ROS may favor human disease such as cancers, cardiovascular diseases, aging, and neurodegenerative diseases [64]. Therefore, the daily intake of exogenous antioxidants is beneficial for protecting the human body against the destructive effects of free radicals [65,66].…”
Section: Antioxidant Compoundsmentioning
confidence: 99%
“…Although preclinical evidence suggests a benefit of antioxidant therapies, antioxidant use in clinical practice is limited and systematic reviews report mixed outcomes of antioxidants. Specifically, conditions investigated by systematic reviews include various cancers [29][30][31][32], diabetes [33,34], cardiovascular disease [35][36][37], and neurodegenerative conditions [38][39][40]. Thus future studies are required to provide robust evidence for the potential of specific pharmaceuticals and cellular therapies, such as hMSCs, as alternative sources of antioxidants to promote antioxidant use in clinical practice.…”
Section: Introductionmentioning
confidence: 97%
“…Trials of agents found in the diet which were thought to have a beneficial impact on prostate cancer have been disappointingly negative 65 . Early randomised studies of the role of beta-carotene in those at high risk of the lung cancer showed an increase in lung cancer, as well as stomach cancer.…”
Section: Introductionmentioning
confidence: 99%